Porphyrin metal complexes and sensitive membrane materials for chemical sensors
By developing porphyrin materials with metal ion composites, the poor solubility and structural instability of existing MOF materials in processing and application have been solved, and the high recognition ability of chemical sensors to organic compound vapors is achieved, especially in high humidity environments, the sensitivity to acetamide is significantly improved.
Patent Information
- Application Number
- JP2023533102
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-07-06
- Filing Date
- 2022-07-01
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2042-07-01
AI Technical Summary
Existing MOF materials have poor solubility and structural instability in processing and application, making it difficult to achieve efficient material synthesis and film preparation, especially the limited ability to identify gases and molecules in chemical sensors.
A porphyrin material with metal ion composite was developed to improve the solubility and porosity of the material by adjusting its structure and chemical bonds, thereby preparing sensitive membranes for chemical sensors.
The high solubility and porosity of the material are achieved, and the recognition ability of chemical sensors to organic compound vapors (such as aldehydes, alcohols, alkenes and aromatics) is improved, especially the sensitivity to acetamide in high humidity environments is significantly improved.
Smart Images

Figure 0007662231000029 
Figure 0007662231000030 
Figure 0007662231000031
Abstract
Description
[Technical field]
[0001] The present invention relates to a porphyrin metal complex and to a sensitive film material for a chemical sensor that recognizes ions and molecules. [Background technology]
[0002] The supramolecular chemistry of porous materials is now a mature field, and several well-defined classes of materials, such as metal-organic-frameworks (MOFs), porous coordination polymers (PCPs), supramolecular assemblies, and porous liquids, have been obtained in the last decades. The advantage of these materials is not only their aesthetically attractive nanostructures, but also their great potential for real-world applications, which are not only based on analogy with purely inorganic porous materials such as zeolites, but also on the wide range of tunable properties that can be achieved by combining organic and coordination chemical synthetic methods. Summary of the Invention [Problem to be solved by the invention]
[0003] With this in mind, the introduction of new porous material constructs or elements is an interesting challenge, especially when improved parameters such as processability or structure properties are required. This is in part because relatively harsh solvothermal conditions are often applied, e.g. for the preparation of MOF materials, which provide excellent textural properties but usually have difficulties in handling. Although progress has been made in processing MOF materials, dissolution methods still have a major gap. Materials that have good solubility while maintaining porosity are required. This would allow easier synthesis of the materials and applications in thin films and coatings, e.g. as sensitive membrane materials for chemical sensors. [Means for solving the problem]
[0004] In accordance with one aspect of the present invention, there is provided a porphyrin metal complex having the structure: [ka] In accordance with another aspect of the present invention, there is provided a porphyrin metal complex having the structure: [ka] In accordance with yet another aspect of the present invention, there is provided a porphyrin metal complex having the structure: [ka] In accordance with yet another aspect of the present invention, there is provided a porphyrin metal complex having the structure: [ka] In accordance with yet another aspect of the present invention, there is provided a porphyrin metal complex having the structure: [ka] In accordance with yet another aspect of the present invention, there is provided a porphyrin metal complex having the structure: [ka] According to yet another aspect of the present invention, there is provided a sensitive film material for a chemical sensor, which uses any one of the above porphyrin metal complexes. Here, the sensitive film material for the chemical sensor may be responsive to organic compound vapors. The organic compound vapor may be one or more organic compounds selected from the group consisting of carbonyl compounds, alcohols, alkenes, and arenes. The organic compound vapor may be acetone. The chemical sensor may also detect a change in a physical parameter of the sensitive membrane. Furthermore, the physical parameter may be one or a combination of parameters selected from surface stress, stress, force, surface tension, pressure, mass, elasticity, Young's modulus, Poisson's ratio, resonant frequency, frequency, volume, thickness, viscosity, density, magnetic force, magnetic quantity, magnetic field, magnetic flux, magnetic flux density, electrical resistance, electrical quantity, dielectric constant, power, electric field, charge, current, voltage, electric potential, mobility, electrostatic energy, capacitance, inductance, reactance, susceptance, admittance, impedance, conductance, plasmon, refractive index, luminous intensity, and temperature. Additionally, the chemical sensor may be a surface stress sensor. Effect of the Invention
[0005] According to the present invention, a group of porphyrin metal complexes having good porosity are provided, and these porphyrin metal complexes are used to provide, for example, sensitive membranes for chemical sensors having useful properties. [Brief description of the drawings]
[0006] [Figure 1] Formation of molecule 1-ox (also referred to as 27c-(Ni) according to the numbering convention of the porphyrin metal complexes of the present invention described below). (a) Chemical structures of molecule 1 (also referred to as 27b-(Ni)) and molecule 1-ox, and a diagram showing how their interconversion was conditioned. See FIG. 2 for the reverse reduction reaction at −0.4 V. (b) Spectroelectrochemical measurements of molecule 1 in 1,2-dichlorobenzene when the solution was maintained at +1.2 V. Note the NIR electronic absorption at 753 nm due to the biradical. (c) Differential pulse voltammetry of molecule 1 in 1,2-dichlorobenzene, showing the initial facile oxidation to molecule 1-ox. (d) Change in molecular configuration from a wavy shape to a highly wrinkled saddle-shaped structure. Side views of these structures obtained by looking at the structures from the direction of the upward arrow near the bottom of the two plan views in the lower row are shown in the upper row. [Diagram 2]Electrochemical measurements of molecule 1-ox. (a) Spectroelectrochemical changes observed during the initial reduction (V = -0.4 V). Note the appearance of several peaks due to molecule 1. The peak at 414 nm decreased in intensity and shifted to 406 nm. The peak at 473 nm increased in intensity. The peaks at 516, 579, 753, and 900 nm decreased in intensity. A new peak appeared at 616 nm. (b) Differential pulsed voltammetry of molecule 1-ox. The three reduction peaks are assigned to the precursor structures shown in (c). An additional oxidation peak at 1.21 V occurred at the characteristic potential for oxidation of the 2,6-di-t-butylpheyl moiety, which is believed to be due to oxidation involving the remaining phenolic meso-substituents. (c) Chemical structures of species resulting from the following reduction series: reduction to molecule 1 at -0.34 V, reduction to Ni-benzimd at -0.88 V, and a species tentatively ascribed to reduction of the N-heterocyclic β-substituent at -1.56 V (although reduction of Ni(II) to Ni(III) may also occur in this region). [Diagram 3] Characterization of molecule 1-ox. (a) 1H NMR of molecule 1-ox in various solvents, namely tetrahydrofuran-d8 (THF-d8), CDCl3 and toluene-d8. (b) Electron spin resonance (ESR) spectra of molecule 1-ox in the solid state at various temperatures. (c) Temperature dependence of the magnetic susceptibility of molecule 1-ox, suggesting a thermally activated singlet-triplet transition. Data fitting was performed using the Bleaney-Bowers equation. (d) Highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) structures of molecule 1-ox in the singlet state. (e) Half occupied molecular orbital (SOMO) structures of molecule 1-ox. [Figure 4A] A complete 1H NMR spectrum of the molecule 1-ox in toluene at 100°C. [Figure 4B]A magnified view of the low field strength region of the 1H NMR spectrum of the molecule 1-ox shown in Figure 4A. [Diagram 5] Temperature dependence of the magnetic susceptibility of molecule 1. Note that the flat response at high temperatures is due to the absence of a singlet-triplet transition. [Figure 6] Simplified X-ray structure of the molecule 1-ox. The molecule is shown as light grey tectons with the t-butyl groups removed. The tectons are the individual porphyrins that self-assemble into the larger structure. Only the structurally important heteroatoms are shown in their respective colours: N: black, O: dark grey, Ni(II): slightly lighter grey. (a) Diagram showing the monomer with spiro-linked units (selected bond distances: 1.888 Å (N-Niav), 1.2381(1) Å (C50-O2), 1.2332(1) Å (C18-O3)). (b) Diagram showing the dimer-1 unit formed by -C≡N-Ni(II) coordination and π-π stacking between the linked heterocyclic units (interaction distances: 3.4674(1) Å (C64...N6: closest approach), 3.0636(1) Å (N(10)-Ni)). (c) Diagram showing the dimer-2 unit formed from the mutual CO...Ni(II) coordination bonds of the biradicals (interaction distance: 3.1205(1) Å (CO...Ni(II)). (d) Diagram showing the formation of a porous structure by the dimer-1 and dimer-2 units. (e) Diagram showing the hydrogen-bond coordination manifold formed in the circled area in (d) (interaction distance: 3.1572(1) Å (O1...N9)). (f) Diagram showing the coordination geometry in Ni(II). (g) Diagram showing the hexagonal pore structure at longer ranges in the crystal (pore dimensions: 6.8 Å × 11.68 Å). See Figures 7 to 15 for ball-and-stick models of similar structures. [Figure 7] X-ray crystal structure of the molecule 1-ox. (a) Plan view of the crystal structure showing a metalloporphyrin with N-heterocyclic unit-spiro hemiquinonoid bond substituents. (b) Saddle-shaped structure of the macrocycle with multiple substituents in a nearly radial configuration at opposing meso positions of the porphyrin. [Figure 8](a)–(c) Diagrams showing the dimer-1 unit of molecule 1-ox. For (a) see Figure 6(b). [Figure 9] Diagram showing the dimer-2 unit of molecule 1-ox formed by alternating saddle-shaped arrangement of biradical units (see Figure 6(c)). [Figure 10] Diagram showing how the dimer units are organized in the molecule 1-ox. The light grey oval region extending from the upper left to the lower right at the top of the diagram shows the dimer-1 units with π-π stacking. The circular grey region near the center of the diagram shows the dimer-2 units with saddle-saddle alternating arrangement with Ni-O coordination. [Figure 11] Diagram showing the X-ray crystal structure of the molecule 1-ox viewed along the a-axis, (a) in ball-and-stick representation, and (b) in space-filling representation. [Figure 12] Diagram showing ball-and-stick representation of the X-ray crystal structure of the molecule 1-ox, (a) view along the b axis, and (b) view along the c axis. [Figure 13] Diagram showing the X-ray crystal structure of the molecule 1-ox viewed along the a-axis. [Figure 14]Diagram showing the wall binding sites of a toluene molecule solvated in the molecule 1-ox. (a) Diagram showing the toluene molecule in light grey and the light grey dashed bonds showing the hydrogen bonds with the nitrile and possible CH...π interactions between its methyl group and the adjacent porphyrin unit. Important distances: methine (H(89))CH...N(9) (2.8872(1) Å), methyl (H85(C))CH...N(10) (3.1945(1) Å), methyl (H(85A))CH...N(9) (2.8872(1) Å), methyl (H85(C))CH...N(10) (3.1945(1) Å, methyl H(85A))CH...C(68) (3.0171(3) Å), methyl (H(85B))CH...C(65) (3.1535(3) Å). The bonds shown as dashed lines in light grey indicate the closest paths from the toluene in dark grey hatched bond units. Important distances (see (b)) are C201...N(8) (3.3461(5) Å), C(203)...C(80) (3.4259(5) Å). (b) Shows stacking of toluene molecules in adjacent cavities in the N-heterocyclic component. (c) Space-filling representation of this stacking. [Figure 15] Diagram showing the wall-binding sites of water. Two water molecules occupy hydrogen-bonding sites on a toluene molecule (shown in grey dashed lines). Important distances (from left): N(10)...OW(2) (3.7303(1) Å), OW(2)...OW(1) (4.3160(1) Å), and N(9)...OW(1) (3.8729(2) Å). Although proton positions are not shown, these distances indicate the hydrogen bonds C≡N...HO between N(9), N(10), and the water molecules interleaved with each other. [Figure 16]Diagram illustrating the porosity and solvent exchange of 1-ox in the crystalline and isolated states. (a) Nitrogen adsorption isotherms of 1-ox(CH2Cl2) (as separated by column chromatography) and 1-ox(crystalline) (crystals grown by cooling a solution of 1-ox in heated toluene to room temperature). (b) Pore half-widths obtained using DFT methods. 1-ox(crystalline) has a fold-pore structure, while 1-ox-(CH2Cl2) lacks porosity at 0.39 nm. (c) Position along the α-axis for a toluene molecule encapsulated in the pores of 1-ox(crystalline). The three crystallographically unique positions (one toluene molecule position randomly arranged in the pore center and the other two in contact with the pore wall) are colored light gray, dark gray (adsorbed by π-π stacking in electron-deficient bonded imidazopyrazine-[2,3]-dicarbonitrile units) and gray (embedded in the pore wall, CH...N≡C interactions and CH...π interactions). (d) Detail of the position of the adsorbed toluene. (e) An unexpected but fortuitous solvent-exchanged water binding site in 1-ox (crystal). (f) The position of HO in the pore that coincides with the "gray" toluene position uniquely bound to the pore wall. See Figures 14 and 15 for further details. [Figure 17] Powder X-ray diffraction patterns for molecule 1-ox obtained by crystallization from toluene (top) and as obtained by evaporation of a solution of 1-ox in chloromethane (bottom). [Figure 18]1 shows the detection response of the MSS with 1-ox sensitive membrane for various vapors at room temperature (25°C). (a) A graph showing the time change in the signal output of the MSS when the sample gas and the purge gas are switched every 30 seconds and supplied to the MSS. (b) A graph showing the normalized relative signal strength for various vapors. (c) A three-dimensional graph showing the humidity dependence of the sensor signal measured for various vapors under five humidity conditions (relative humidity of the measured vapor) at room temperature (25°C). In this graph, the relative humidity is 0, 10, 40, 70, and 90% RH from the front to the back. (d) A three-dimensional graph showing the detection limit (LOD) of the MSS with 1-ox sensitive membrane for various vapors measured under the various humidity conditions (relative humidity of the measured vapor) shown in (c) at 25°C. Here, as in (c), the relative humidity is 0, 10, 40, 70, and 90% RH from the front to the back of the graph. [Figure 19] Figures showing the detection response of the MSS with a sensitive membrane using molecule 1 at room temperature (25 °C) for various vapors. (a) Graph showing the time change in the signal output of the MSS when the sample gas and purge gas were supplied to the MSS by switching them every 30 seconds. (b) Graph showing the normalized relative signal intensity for various vapors. [Figure 20] The figure shows the detection signals of the MSS with 1-ox sensitive membrane measured at room temperature (25°C) for various vapors at various relative humidities: (a) water, (b) acetone, (c) ethanol, (d) chloroform, (e) heptane, (f) ethyl acetate. In the measurement result for acetone shown in (b), the curves for relative humidity of 40% and 70% almost overlap. [Figure 21] 1 shows the detection response of the MSS with a 42b-(Ni) sensitive film to various vapors at room temperature (25°C) for "Measurement 1" in the example. DMSO was used as the solvent when the sensitive film was prepared. (a) A diagram showing the change in signal output of the MSS over time when the sample gas and purge gas were supplied to the MSS by switching them every 30 seconds. (b) A diagram showing the average signal intensity for various vapors. [Figure 22]1 shows the detection response of the MSS with a 42b-(Ni) sensitive film to various vapors at room temperature (25°C) for "Measurement 2" in the example. Toluene was used as the solvent when the sensitive film was prepared. (a) A diagram showing the change in signal output of the MSS over time when the sample gas and purge gas were supplied to the MSS by switching them every 30 seconds. (b) A diagram showing the average signal intensity for various vapors. [Figure 23] 1 shows the detection response of the MSS with a 42c-(Ni) sensitive film to various vapors at room temperature (25°C) for "Measurement 3" in Example 1. DMSO was used as the solvent when the sensitive film was prepared. (a) A diagram showing the change in signal output of the MSS over time when the sample gas and purge gas were supplied to the MSS by switching them every 30 seconds. (b) A diagram showing the average signal intensity for various vapors. [Figure 24] Graph showing the detection response of the MSS (Ch4) with a 21c-(Ni) sensitive film to various vapors at room temperature (25°C) for "Measurement 4" in the example. DMF was used as the solvent when the sensitive film was prepared. (a) Graph showing the change in signal output of the MSS over time when the sample gas and purge gas were supplied to the MSS by switching them every 30 seconds. (b) Graph showing the average signal intensity for various vapors. [Diagram 25] For "Measurement 5" in the embodiment, the figure shows the detection response of the MSS with 21c-(Ni) sensitive film to the vapor of isopropyl alcohol and toluene-containing isopropyl alcohol solution (toluene concentration: 10-5M) at room temperature (25°C). Dry nitrogen gas was used as the purge gas and carrier gas. (a) Ch1, (b) Ch2, (c) Ch3, (d) Ch4. [Figure 26] 25A to 25D are diagrams showing the results of "Measurement 5" in the embodiment, in which wet nitrogen gas was used as the purge gas and carrier gas. The distinction between (a) to (d) is the same as in FIG. 25. [Figure 27](a) and (b) are diagrams showing the detection response of the MSS (Ch2 and Ch1) with the 21c-(Ni) sensitive film to the vapor of a toluene-containing isopropyl alcohol solution (toluene concentration: 10-5 M to 10-1 M) at room temperature (25 ° C.) for "Measurement 5" in the example. Dry nitrogen gas was used as the purge gas and carrier gas. (c) and (d) are diagrams showing the detection response when wet nitrogen gas was used as the purge gas and carrier gas. The detection response to the vapor of pure isopropyl alcohol is also shown. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0007] In stark contrast to porous nanomaterials, there exists a class of organic compounds known as biradicals. Biradicals have unpaired electrons located at various sites on the molecule, which gives them unique optical and magnetic properties. Such properties arise as a result of the molecule having moieties that support a lone radical electron (e.g., the versatile active antioxidant phenols, e.g., 2,6-di-t-butlyphenol) or due to the unique electronic structure of the molecule (e.g., acenes with many rings, such as heptacene). The biradical character of these molecules generally results in a particular reactivity or instability (e.g., reactivity to O2 or HO), but can be stabilized when contained in a medium, such as in a crystal or on a surface. This is demonstrated here by incorporating a somewhat unstable molecule into a persistent microporous crystalline network. This application presents a rare example of a solution-processable porous compound that provides stable biradicals, whose properties include unique magnetic and optical properties. Further adding to the novelty of this system is the thermally and solution modulated behavior of the biradical position, with the unpaired electron being shared between supporting elements and ultimately controlled by temperature.
[0008] One of the applications of the porous biradical material according to the present invention is a sensitive film for a chemical sensor for selectively responding to and detecting a solvent vapor or the like. In an exemplary embodiment, the material according to the present invention exhibits excellent sensitivity and selectivity to one or more organic compounds selected from the group consisting of carbonyl compounds, alcohols, alkenes, and arenes. In a more specific embodiment, the material according to the present invention exhibits excellent sensitivity and selectivity to acetone even under high humidity, which provides great potential for applications in the biomedical field, such as monitoring acetone.
[0009] In the course of investigating the chemical synthesis properties of meso-tetrakis(3,5-di-t-butyl-4-hydroxyphenyl)porphyrin (TDtBHPP), the inventors have found a novel molecule with two peripheral substituents linked to the porphyrin via a spiro-type linkage (containing a single quaternary carbon atom, with two heterocycles connected only by this carbon atom). An intramolecular process leads to a reaction between adjacent substituents, which fuse to form a spiro structure, resulting in molecule 1, shown in Figure 1. This molecule 1 is a precursor to molecule 1-ox, shown below. Molecule 1 is easily oxidized and can be further oxidized using 2,3-dichloro-5,6-dicyano-p-benzoquinone (DDQ) to form molecule 1-ox. Molecule 1-ox exists as an open shell biradical, as shown in Figure 1(b) by electronic absorption at 753 nm in the near infrared region. This electronic absorption appears during spectroelectrochemical measurements of a solution of molecule 1 held at a potential of 1.2 V (initial oxidation, see differential pulse voltammetry (DPV) in Fig. 1(c)). Figure 1(d) shows a comparison of the X-ray crystal structures of molecules 1 and 1-ox, where the oxidation is indicated by a significant structural change from a slightly wavy structure (molecule 1) to a saddle-shaped shape (molecule 1-ox), which was initially assigned to a closed-shell structure.
[0010] As a result of further research, the inventors of the present invention have found that, in addition to the above-mentioned molecule 1,1-ox, a porphyrin derivative metal complex having a similar structure, as described below, also exhibits properties similar to those of the above-mentioned molecule 1,1-ox.
[0011] <General structural formula of the porphyrin metal complex according to the present invention> The general structural formula of the porphyrin metal complex according to the present invention is shown below. The porphyrin metal complex has three oxidation states (denoted by a, b, and c) and can be classified as benzimidazole-substituted and imidazole-substituted. Since these complexes have many possible substituents and are complex in structure, the numbering rules for the structures of these metal complexes are shown below before showing the structural formula.
[0012] [ka]
[0013] These structural formulas are shown below, classified according to the combination of oxidation state and substituent.
[0014] I. Structural formula of benzimidazole-substituted complexes of oxidation state a
[0015] [ka]
[0016] II. Structural formulas of benzimidazole-substituted complexes of oxidation state b
[0017] [ka]
[0018] III. Structural formulas of benzimidazole-substituted complexes of oxidation state c
[0019] [ka]
[0020] IV. Structural formulas of imidazole-substituted complexes in oxidation state a
[0021] [ka]
[0022] V. Structural formula of imidazole-substituted complexes of oxidation state b
[0023] [ka]
[0024] VI. Structural formulas of imidazole-substituted complexes in oxidation state c
[0025] [ka]
[0026] Here, the molecules 1 and 1-ox of the first porphyrin metal complex are given the identification numbers 27b-(Ni) and 27c-(Ni), respectively, according to the numbering rules mentioned above.
[0027] <Method of producing porphyrin metal complex> An example of a method for producing a porphyrin metal complex according to the present invention having the above-mentioned structure will be described below step by step.
[0028] Step 1: Start of porphyrin synthesis First, the starting porphyrin is used to form complexes with the central metal Ni(II), Cu(II) or Pt(II), where Ni(II) and Cu(II) are provided as acetates and Pt(II) is provided as PtCl2.
[0029] [ka]
[0030] Step 2: Formylation of specific metalloporphyrins TDtBHPP(M) (M = Ni(II), Cu(II), Pt(II)) Using the method disclosed in Non-Patent Document 2, a formyl group (-CHO) is introduced into the porphyrin 2 position of TDtBHPP(M) (M = Ni(II), Cu(II), Pt(II)).
[0031] Here, the porphyrin TDtBHPP (Non-Patent Document 1) is dissolved in CHCl3. To do this, 10 equivalents of Cu(OAc)2·H2O dissolved in a minimum amount of methanol are added and the mixture is refluxed for 40 minutes and then cooled to room temperature. The solution is then separated from the water. The organic phase is separated and dried over anhydrous sodium sulfate. The solution is filtered to remove the sodium sulfate and the solvent is removed under reduced pressure. The remaining crude product is purified by column chromatography on a silica column eluted with CHCl3 to obtain the compound TDtBHPP(M).
[0032] Example 1: The Ni(II) complex is prepared by refluxing the porphyrin (TDtBHPP) with Ni(OAc)2·4H2) (10 equiv.) in DMF (N,N-dimethylformamide) for 2 h, followed by precipitation with water. The resulting crude product is purified on a silica column using CHCl3 as the eluent.
[0033] Example 2: Pt(II) complex is prepared by refluxing porphyrin (TDtBHPP) with PtCl2 in benzonitrile for 12 hours. The resulting crude product is purified on a silica column using CHCl3 as the eluent.
[0034] [ka]
[0035] Step 3: Condensation of 2-formylated porphyrin with 2-phenylenediamine According to Non-Patent Document 3, 2-formylated porphyrins are condensed with o-phenylenediamine. These imidazole / benzimidazole products are in the oxidation state "a" among the oxidation states mentioned in the complex numbering rule above. This gives porphyrin metal complexes according to the present invention with central metals Ni(II), Cu(II), Pt(II) in the oxidation state a.
[0036] [ka]
[0037] Step 4: Introduction of spiro groups by intramolecular oxidation reaction DDQ is used as the oxidizing agent. 2,3-Dichloro-5,6-dicyano-1,4-benzoquinone (4.0 equiv.) is added to a solution of the benzimidazole-substituted product from the previous reaction (1 equiv.) in dichloromethane and the resulting mixture is stirred for 2 h. The reaction mixture volume is reduced to a suitable volume and separated on a chromatographic column (SiO2) using CH2Cl2 as the eluent to give the product with oxidation state "b". Further elution with CH2Cl2 also gives the product with oxidation state "c".
[0038] [ka]
[0039] Step 5: Demetallation reaction The metalloporphyrin to be demetallated is dissolved in CHCl3 and concentrated sulfuric acid is added dropwise with vigorous stirring at 0°C, followed by stirring at 0°C for 1 hour. At the end of this time period, distilled water is added. The organic layer is separated and neutralized with 25% aqueous ammonia. The organic layer is dried over anhydrous sodium sulfate and concentrated to a small volume. It is purified by silica gel chromatography using CHCl3 as the eluent.
[0040] [ka]
[0041] Step 6: Remetallization with other metals Metal complexes with other metals are prepared by the following method. · Co(II) and Zn(II) complexes: The products from step 5 are refluxed separately with acetates Co(OAc)2 and Zn(OAc)2 (dissolved in a minimum of methanol) for 2 h. Now, Co(OAc)2 and Zn(OAc)2 dissolved in a minimum of methanol are added dropwise to the CHCl3 solution of porphyrin. The obtained crude products are purified on a silica column using CHCl3 as the eluent. ·Mn(III)Cl complex: 10 equivalents of MnCl2·4H2 are refluxed in pyridine and N,N-dimethylformamide at 153 °C, then purified using column chromatography on silica with CHCl3 as eluent. ·V=O complex: This complex is prepared using VOSO4 and refluxed in N,N-dimethylformamide under argon atmosphere and then purified using column chromatography on silica with CHCl3 as eluent. · Al(III)Cl complex: This complex is prepared according to the method described above using diethylaluminum chloride (EtAlCl) dissolved in dichloromethane. · Sn(IV)Cl2 complex: Metallation of H2-1 with SnCl2 in pyridine according to (6) gives the dichlorinated Sn(IV) porphyrin. Pb(II) complexes: Lead(II) porphyrins can be prepared by refluxing lead(II) acetate and free base porphyrin in pyridine or DMF for a short period (5-10 min) according to non-patent literature 7 and 8. Silicon(IV) complex (porphyrin Si(IV)Cl2): prepared according to non-patent document 9. Pd(II) complex: Pd II The -porphyrin complexes are synthesized by heating and refluxing H2-1 with the corresponding precursor PdCl2(NCPh)2 in degassed benzonitrile according to the method of Non-Patent Document 10. Fe(III)Cl complex: This complex is prepared according to the method described in J. Chem. Soc. 1999, 143:1311-1323.
[0042] In other words, in this step, the central metals Ni(II), Cu(II), and Pt(II) are removed from the complex in oxidation state b in step 5, and Ti=O, V=O, Mn(II), Fe(II), Co(II), Zn(II), Pd(II), Al(III)Cl, Mn(III)Cl, Fe(III)Cl, Si(IV)Cl2, Sn(IV)Cl2, Pb(II), and Pb(IV)Cl2 are then bonded to the compound as central metals.
[0043] [ka]
[0044] Step 7: Oxidation of metal complexes When PbO2 is used as the oxidizing agent: Lead oxide (4.0 equiv.) is added to a stirred dichloromethane solution of the benzimidazole-substituted product from the previous reaction (1 equiv.) and the resulting mixture is stirred for an additional 2 h. The reaction mixture is reduced to a suitable volume and then subjected to column chromatography (SiO2) using CH2Cl2 as the eluent to obtain the compound in the oxidation state designated "c".
[0045] From compound "a": To a stirred solution of compound "a" (1 eq) in dichloromethane, add lead oxide (4.0 eq) and stir the resulting mixture for an additional 2 h. Reduce the volume of the reaction mixture to an appropriate volume and then subject to column chromatography (SiO2) using CH2Cl2 as the eluent to obtain compound in oxidation state "c".
[0046] This procedure produces a complex of oxidation state c from a complex of oxidation state b obtained by the above-mentioned procedure 6 or procedure 4.
[0047] [ka]
[0048] <Sensing membrane for chemical sensors using the porphyrin metal complex according to the present invention> The porphyrin metal complex according to the present invention described above adsorbs and absorbs various gases and the like due to its porosity, and various physical properties (parameters) change depending on the presence or absence of adsorption and the amount of adsorption and absorption. Examples of such physical parameters include, but are not limited to, surface stress, stress, force, surface tension, pressure, mass, elasticity, Young's modulus, Poisson's ratio, resonance frequency, frequency, volume, thickness, viscosity, density, magnetic force, magnetic quantity, magnetic field, magnetic flux, magnetic flux density, electrical resistance, electrical quantity, dielectric constant, power, electric field, charge, current, voltage, potential, mobility, electrostatic energy, capacitance, inductance, reactance, susceptance, admittance, impedance, conductance, plasmon, refractive index, luminous intensity, and temperature. The porphyrin metal complex according to the present invention can be used as a sensitive film material for any type of sensor that responds to a change in one or more of such parameters due to a sample gas. In the examples described later, as an example of a sensor, a membrane-type surface stress sensor, which is a type of surface stress sensor, is used as a sensitive film, and it is shown that this configuration has high sensitivity to vapors of various organic compounds, especially acetone, even under high humidity. Note that, since the response characteristics to various gases were not verified for all gases, there is a possibility that the sensor may respond strongly to gases other than acetone depending on the measurement conditions, and it goes without saying that this does not exclude the possibility that the sensor may be effectively used to detect those gases.
[0049] In addition, the suitability as such a sensitive film is not limited to 27c-(Ni), and it goes without saying that similar characteristics can be obtained with sensitive films using other porphyrin metal complexes according to the present invention having similar structures. In fact, in the examples described later, porphyrin metal complexes having structures different from 27c-(Ni) (different combinations of oxidation states and substituents) were synthesized, and these were used as sensitive films of film-type surface stress sensors, and the results of analyzing the response characteristics to the vapors of various organic compounds were also shown. EXAMPLES
[0050] [Structures and properties of porphyrin metal complexes] The structure and properties of the porphyrin metal complex according to the present invention will be described in more detail below, taking the above-mentioned molecules 1 and 1-ox as examples.
[0051] The biradical form of the molecule 1-ox is initially 1 This was revealed by H NMR measurements (see Fig. 3(a) and Fig. 4A, 4B). It is known that meso-substituent resonances are broadened when the meso-substituent has significant radical character. For molecule 1-ox, this situation is complicated by the presence of up to four substituents that can support radicals. In Fig. 3(a), protons a (spiro-quinone), b (phenol), c, and d (biradical) are broadened depending on the solvent. In tetrahydrofuran-d8, a and c are broadened (b and d are sharp). This suggests that the biradical is mainly located on the spiroquinone and is more distant from the adjacent meso-substituents. In CDCl3, the resonances due to a, c, and d are all broadened to some extent due to the delocalization of the biradical character at these positions. On the other hand, in toluene-d8, a and b are equally sharp, while only d and c are broadened. This indicates that a single species with biradical character is distributed laterally across the molecule. Therefore, to avoid complications arising from mixing of biradical configurations, toluene was chosen as the solvent for all workup of molecule 1-ox.
[0052] The electron spin resonance (ESR) spectrum shown in Figure 3(b) is characteristic of the phenoxyl radical at all temperatures, with a structure appearing above 300 K. The magnetic susceptibility of the molecule 1-ox in the solid state, shown in Figure 3(c), is calculated using the Bleaney-Bowers equation to be −2J=692.1 cm -1 The temperature-dependent singlet-triplet properties can be fitted as . The fit is less satisfactory above 250 K, which is probably due to intramolecular processes. The data also show a broad peak in the range of 50 K to 150 K. One might attribute this peak to another singlet-triplet state at low temperatures, but no associated structural change could be detected between the structures measured at 113 K and 200 K. Furthermore, molecule 1, the precursor of molecule 1-ox, shows a similar response, albeit mainly diamagnetic (see Figure 5). This indicates that it is due to other phenomena, possibly related to the ligand interactions around the Ni(II) cation. This feature is currently under investigation. DFT calculations of the molecular orbital structure of molecule 1-ox shown in Figure 3(d) reveal that the highest occupied molecular orbital of molecule 1-ox in the singlet state is distributed over its quinone-like substituents facing each other. The lowest unoccupied molecular orbital is found to be on the electron deficient side of the molecule, indicating substantial D-π-A character. For the triplet state, non-degenerate half-occupied orbitals are also distributed over the biradical moiety.
[0053] The X-ray structure of the compound, measured at 113 K, was obtained by cooling a heated solution of the molecule 1-ox in toluene. The molecule is illustrated in the form of a stylized model due to its complex interactions. See Figures 7-15 for detailed ball-and-stick models of the overall structure. The structure consists of two different types of dimer unit interactions, with allied double mutual nitrile-phenol hydrogen bonding completing the system. The saddle-shaped 1-ox molecule shown in Figure 6(a) undergoes two different dimer interactions. Here, dimer-1 shown in Figure 6(b) is formed from mutual nitrile-Ni(II) coordinate bonds, reinforced by π-π stacking between flat, electron-deficient dintrile-substituted (2,3-dicarbonitrile-substituted) linked heterocyclic units. Dimer-2 shown in Figure 6(c) is formed from mutual CO...Ni(II) coordinate bonds with biradical meso-substitution. These dimer interactions lead to the pore structure shown in Figure 6(d), whose formation also relies on nitrile-phenol hydrogen bonds shown in Figure 6(e). The coordination configuration at Ni(II) is shown in Figure 6(f) and the growth of the bulk porous structure by the assembly of these interactions is shown in Figure 6(g). In Figure 6, the molecules shown in light grey are shown with their t-butyl groups removed for clarity. In Figure 6(g), the molecules shown in grey contain t-butyl groups, but the presence of these groups shows only a small impairment of porosity. The importance of this structure lies in the fact that it forms directly from solution without the need for solvothermal treatment.
[0054] Crystals of coordination complexes grown using ambient solution techniques tend to lose their structural integrity when removed from their mother liquor, and as a result, structural features such as pores are usually lost. In the case of molecule 1-ox, we surprisingly found that the porosity was maintained even after removing the toluene contained in the structure by drying at 120 °C under reduced pressure for 24 hours. The textural properties of molecule 1-ox after such treatment were measured using N2 adsorption isothermometry and are shown in Figures 16(a) and (b). Important parameters derived from this data are listed in Table 1. Figure 16(c) shows the toluene encapsulated in the pores of molecule 1-ox as viewed along the a-axis of the crystal. Three moles of toluene are bound per unit cell, each located at a unique site. Specifically, a. it is bound in the pore cavities (light grey), b. it is adsorbed by π-π stacks of electron-deficient bonded imidazopyrazine-[2,3]-dicarbonitrile units (dark grey, see also Figure 16(d)), and c. it is buried in the CH...N≡C and CH...π interactions on the pore walls (grey, see also Figure 16(d)).
[0055] [Table 1]
[0056] During X-ray crystallography, it was determined that toluene solvent molecules are present in the structure in various stoichiometric situations, which indicates that the crystals are 475 nm in diameter. 2 g -1This suggests that toluene can be removed from the pores, as suggested by the large surface area measured (Table 1). Indeed, if the solvent is allowed to evaporate from a sample of crystals stored in mineral oil, the integrity of the crystals is not compromised, and when the crystals are cooled to a temperature suitable for X-ray crystal diffraction, the same structure is found to now accommodate 2 moles of HO per unit cell (Figure 16(e), (f)). In particular, water molecules replace toluene (grey) molecules in the pore wall binding sites. Moreover, an isolated sample of 1-ox obtained by evaporation of its solution in dichloromethane also exhibits a large surface area (approximately 350 m 2 g -1 , Table 1), suggesting that solvation with toluene is not essential to establish the porous structure of 1-ox. Interestingly, 1-ox(CH2Cl2) not only has a smaller surface area, but also lacks the smallest pores (half-width 0.392 nm) that appear in 1-ox(crystalline), suggesting that the specific binding sites of 1-ox(CH2Cl2) are already occupied (powder diffraction, Figure 17).
[0057] The solvent exchange property of 1-ox based on its permanent porous structure enables its application to solvent detection using the Membrane-type Surface stress Sensor (MSS) platform. The MSS is a nanomechanical sensor made of a silicon membrane embedded with four piezoresistors. This silicon membrane is covered with a sensitive membrane, and the surface stress caused by the adsorption of volatile gas molecules on the sensitive membrane is used for detection. The surface stress thus caused is converted into a measurable detection signal by the piezoresistors. Here, a DMF solution of 1-ox was deposited on the silicon membrane of the MSS using a micro-inkjet technique, and the DMF was removed by evaporation to prepare an MSS with a 1-ox sensitive membrane. Note that the MSS itself is a sensor well known to those skilled in the art, so a detailed description will not be given here, but please refer to, for example, Patent Document 1 if necessary.
[0058] The MSS with the 1-ox sensitive membrane thus prepared was used to measure the selectivity and sensitivity for various organic compound vapors at room temperature (25°C). Specifically, the time change in the signal output of the MSS was measured when the sample gas and the purge gas were switched every 30 seconds and supplied to the MSS. Here, the sample gas is a mixed gas in which dry nitrogen gas is fed as a carrier gas at a flow rate of 20 sccm into a vial containing the organic compound to be measured, and the headspace gas of the vial, which is the saturated vapor of the organic compound, is sent out from the vial and mixed with dry nitrogen gas at a flow rate of 80 sccm to make a total flow rate of 100 sccm. In other words, the sample gas supplied to the MSS is a saturated sample gas (headspace gas) in which the organic compound vapor to be measured is saturated in nitrogen gas, that is, a "nitrogen-organic compound mixed gas" in which the vapor pressure of the organic compound to be measured (partial pressure of the organic compound) is the saturated vapor pressure of the organic compound, diluted 1 / 5 with pure nitrogen gas. As the purge gas, only dry nitrogen gas was used, and the flow rate was set to 100 sccm.
[0059] Figure 18(a) shows the initial detection response of the MSS with 1-ox sensitive membrane to water vapor, alcohols, carbonyl compounds, alkenes, and arenes. As shown in this figure, a very rapid response (within a few seconds) and measurable signals of various intensities were observed for all vapors. Although the signal for acetone did not reach the saturated value even after 30 seconds of continuous vapor application, it output the largest signal among the measured VOC vapors and showed a very strong response. In addition, a rapid and strong response was also observed for alcohols.
[0060] The sensitivity of the 1-ox membrane is almost four times higher than that of the membrane using molecule 1 shown in Fig. 19(a). This is due to the surface stress caused by the significant amount of adsorption of molecule 1-ox into the nanoporous structure. Of course, the composition and flow rate of the sample gas and purge gas, as well as the purge-sampling cycle, supplied to the MSS with the membrane using molecule 1 are the same as those described above for the measurement using the MSS with the 1-ox membrane. Due to the similarity of the molecular structures, the sensitivity of these two types of membranes to various vapors is similar (Fig. 19(b)). Fig. 18(b) shows the normalized relative intensity for all vapors. Interestingly, the sensitivity to water vapor is very low (1 / 16) compared to that to acetone vapor, because water vapor has only minimal interaction with the porous 1-ox membrane. In addition, the crystal structure of 1-ox contains two water molecules in its cavity, which restricts the inclusion of more water into the nanoscale cavity. This kind of feature is very important for any kind of gas or vapor sensor for real-time measurement under high humidity. For example, there is a great demand for analyzing gases obtained from living bodies, which almost always contain a considerable amount of water vapor, such as gases exhaled or emitted from the skin. In addition, most gases that can be considered as analysis targets, such as exhaust gases and leaking gases from machines, and even the atmosphere, contain water vapor, and the water vapor content is not necessarily constant in many cases. Therefore, it is very desirable to provide a sensitive film material that can easily realize a sensor that has high sensitivity to a specific gas and very low sensitivity to water vapor.
[0061] Furthermore, the 1-ox sensitive membrane shows a strong response to alcohols (methanol, ethanol), which can be attributed to the replacement of water molecules with various small molecules containing hydroxyl groups. It shows an intermediate response to aromatic (toluene) and alkene (hexane, octane) vapors, which is due to the low vapor pressures and large molecular sizes of these substances, as well as the different diffusion rates of these classes of VOCs. Detailed experiments of the sensitivity under various humidity conditions (0-90%) were performed for 10 vapors containing similar functional groups.
[0062] Figure 18(c) shows the sensitivity to various vapors under various humidity conditions. Interestingly, the sensitivity seems to improve for all vapors with increasing humidity up to 70%. When the humidity is further increased from 70%, the sensitivity at 90% humidity is also higher than that at 0% humidity. Again, the sensitivity of acetone vapor at various humidities is the highest compared to the sensitivity for other vapors containing carbonyl groups. The detection limits (LODs) of these various vapors were calculated by multiplying the VOC concentration corresponding to 10% saturated vapor by the ratio of the inherent noise level of the MSS measurement system (around 1 μV) to the average output voltage of three consecutive purge-sampling cycles.
[0063] Figure 18(d) shows the detection limit of the 1-ox-coated MSS, where a good detection limit of less than 2 ppm for acetone vapor is shown even under 90% humidity conditions. In addition, for most of the other vapors, the sensor platform shows LODs of less than 10 ppm even at the highest humidity levels. However, the detection limit of hexanol is even lower than that of acetone, which is associated with the detection signal being detectable even at low vapor concentrations. It should be noted that a longer exposure time of the sensor to the vapors can produce a larger signal, since the signal did not reach the saturation point during the purge-sampling cycle in the experiments performed here, as can be seen in Figure 20 and elsewhere. Thus, the detection limit can be extended to a smaller sub-ppm range by increasing the exposure time.
[0064] <Consideration> Introducing macrocyclic saddle-shaped or bent configurations into tetrapyrroles has sometimes been seen to result in porous structures, but such configurations are generally not permanent, and so far no porphyrin system with a saddle-shaped configuration has been found that most closely resembles the molecule 1-ox. The saddle-shaped macrocycle should improve the possibility of forming structural voids, but the molecule 1-ox undergoes several interactions in its structure. Some of these are face-to-face π-π stacking dimerizations, which lead to the formation of doubly recessed "secondary building units (SBUs)". In this case, it is important to consider the availability of SBU inter-dimer interactions, especially those involving electronegative atoms that may coordinate to the Ni(II) cation. In 1-ox, such interactions are provided by the substituent oxygen atoms, whose CO bond distances form a Ni(II) anion biradicaloid unit long enough for the metalloporphyrin unit to coordinate to the Ni(II) anion (i.e., the bulky t-butyl group normally prevents the phenolic oxygen atom from interacting with other entities, here the Ni atom, but in the present compounds the formation of the biradical increases the phenolic bond length, which facilitates interaction with the Ni atom, etc.). It is therefore interesting to consider whether similar non-biradical species also form extended coordination structures. This will probably become clear when other differently structured derivatives of these compounds become available. Overall, the molecule 1-ox forms its stable porous network morphology with the best of the intermolecular mutual effects of π-π stacking / Ni(II)-nitrile coordination dimerization and Ni(II)-carbonyl coordination dimerization, with the assistance of the structure of the combined OH...nitrile hydrogen bond manifold and other CH...X interactions. This illustrates the benefit of multipoint cooperativity in establishing stable porous structures in supramolecular solvent processable systems.A porous sensing membrane with an interconnected supramolecular structure is highly desirable for strain-induced microelectromechanical system (MEMS) sensors used for multi-component gas or vapor detection. However, most of the materials in this category are highly inert and extremely difficult to disperse in any kind of solvent. In this respect, microporous 1-ox, with its solvent exchange properties and ease of solution processability, is a natural choice of sensing membrane for strain-induced sensors. Highly sensitive MSS platform with 1-ox sensing membrane provided fast and strong signals for various VOCs. Of course, other types of strain-induced sensors, not limited to MSS, are affected by the inherent properties of these sensors, but it goes without saying that they benefit from the selectivity, sensitivity, etc. provided by the 1-ox sensing membrane. Most importantly, this sensing membrane material has a very low sensitivity to water vapor due to the presence of water molecules in the micropore cavities. Selectivity to acetone is another important property of the sensing membrane using this material. This may be related to the effective replacement of water molecules in the micropore cavities or the sustainable acetone-water interaction. Moreover, this kind of solution-processable micropore-sensitive membrane with selectivity to various biomarkers is of great importance for real-time applications such as biomedical diagnosis and food quality control.
[0065] <Conclusion> The open-shell biradical 1-ox is porous in the crystalline solid state, and the porosity of this compound allows the removal of toluene and re-adsorption of water, thus enabling the solvent exchange described above. The sites where solvent adsorption occurs are provided by hydrogen bonding, π-π stacking interactions, and solvent enrichment within the tubular cavities in the remaining structure. These properties suggest applications in selective solvent adsorption and sensing. For sensing, an MSS measurement system was used to demonstrate the extended selectivity of 1-ox in the solid state for acetone detection. The most notable feature of 1-ox is its apparent ability to form porous structures by simple solution casting methods, making this compound series suitable for a variety of sensing and other applications. The formation of this molecule provides some interesting guidance for the design of next-generation materials. Here, the change in morphology (i.e., saddle-shaped structure) induced by the oxidation of molecule 1 and the significant lack of molecular symmetry are particularly important for the activity of self-assembly into porous states.
[0066] [Synthesis and properties of porphyrin metal complexes with different structures] Next, the synthesis and properties of porphyrin metal complexes having structures different from those of the above-mentioned molecules 1 and 1-ox will be described. This will make it clearer that this compound system is useful as a sensitive film material for various chemical sensors. In the following, the above-mentioned identification numbers will be used to easily distinguish each molecule. Therefore, molecules 1 and 1-ox will be referred to as 27b-(Ni) and 27c-(Ni), respectively.
[0067] <Synthesis of 21a-(Ni)>
[0068] [ka]
[0069] A mixture of [T(DtBHP)PNi]-CHO (200 mg, 0.16 mmol) and 2,3-diaminophenazine (69 mg, 0.33 mmol) in DMF (10 mL) was refluxed under nitrogen atmosphere for 24 h. After completion of the reaction, the mixture was cooled to room temperature and the solvent was removed under reduced pressure. The remaining crude product was purified by column chromatography (SiO2) using a mixture of CHCl:MeOH (99:1) as the eluent to give 21a-(Ni) as a dark green solid (yield: 165 mg, 71%).
[0070] <Synthesis of 21b-(Ni) and 21c-(Ni)>
[0071] [ka]
[0072] In a round-bottom flask, 200 mg (0.14 mmol) of 21a-(Ni) obtained as described above was dissolved in 20 mL of CHCl, and 130 mg (0.57 mmol) of DDQ was added. The mixture was stirred at room temperature for 1 h and the solvent was removed under reduced pressure. The remaining crude product was purified by column chromatography (AlO) using CHCl as eluent to give 21b-(Ni) as a green solid from the first fraction (yield: 22 mg, 11%), followed by 21c-(Ni) as a brown solid from the second fraction (yield: 50 mg, 25%).
[0073] <Synthesis of 42a-(Ni)>
[0074] [ka]
[0075] A mixture of [T(DtBHP)PNi]-CHO (400 mg, 0.33 mmol) and 5,6-bis(4-bromophenyl)pyrazine-2,3-diamine (278 mg, 0.66 mmol) in DMF (20 mL) was refluxed under nitrogen atmosphere for 24 h. After completion of the reaction, the mixture was cooled to room temperature and the solvent was removed under reduced pressure. The remaining crude product was purified by column chromatography (SiO2) using a mixture of CHCl:Hexane (7:3) as eluent to give 42a-(Ni) as a dark green solid (yield: 280 mg, 53%).
[0076] <Synthesis of 42b-(Ni) and 42c-(Ni)>
[0077] [ka]
[0078] In a round-bottom flask, 100 mg (62 μmol) of 42a-(Ni) obtained as described above was dissolved in 10 mL of CHCl, and 56 mg (0.25 mmol) of DDQ was added. The mixture was stirred at room temperature for 1 h, and the solvent was removed under reduced pressure. The remaining crude product was purified by column chromatography (SiO) using CHCl as the eluent to give 42b-(Ni) as a green solid (yield: 32 mg, 32%). It was then purified using a more polar eluent of CHCl:methanol (199:1) to give 42c-(Ni) as a brown solid (yield: 28 mg, 28%).
[0079] The gas adsorption measurements were carried out by nitrogen gas adsorption method for 21b-(Ni), 21c-(Ni), 42b-(Ni), 42c-(Ni), 27b-(Ni), and 27c-(Ni) obtained as described above, and the specific surface area (BET method), pore size distribution, and pore volume (BJH method) were evaluated. The results are shown in Table 2.
[0080] [Table 2]
[0081] Comparing molecules with the same substituents but different oxidation states, the complexes with oxidation state c, 27c-(Ni) and 27b-(Ni), and 21c-(Ni) and 21b-(Ni), have larger BET specific surface areas, smaller average pore diameters, and larger BJH pore volumes than the complexes with oxidation state b. Interestingly, the opposite tendency was observed for 42c-(Ni) and 42b-(Ni).
[0082] <Response characteristics to organic compound vapors> [Measurement 1] A DMSO (dimethyl sulfoxide) solution of 42b-(Ni) was prepared and deposited on the silicon membrane of the MSS using micro-inkjet technology, and the DMSO was removed by evaporation to produce an MSS with a 42b-(Ni)-sensitive membrane. Here, the number of droplets of the DMSO solution on the silicon membrane of the MSS was 300.
[0083] The selectivity and sensitivity to various VOC vapors at room temperature (25°C) were measured using the prepared MSS with 42b-(Ni) sensitive membrane. Here, ethyl acetate, acetone, ethanol, hexane, and toluene were used as VOCs, and the composition and flow rate of the sample gas and purge gas supplied to the MSS, as well as the conditions of the purge-sampling cycle, were the same as those described above for the measurement using the MSS with 1-ox sensitive membrane. As a control, wet nitrogen gas containing water vapor was used instead of the sample gas containing VOC vapor. Specifically, this wet nitrogen gas was produced by blowing dry nitrogen gas into water at a flow rate of 100 sccm.
[0084] [Measurement 2] An MSS with a 42b-(Ni)-sensitive film was prepared using the same procedure as in Measurement 1 above, except that toluene was used as the solvent when depositing 42b-(Ni) on the silicon film of the MSS, and measurements were performed on the same sample gas and control gas as in Measurement 1.
[0085] [Measurement 3] Using 42c-(Ni), an MSS with a 42c-(Ni) sensitive film was prepared in the same manner as in Measurement 1 above, and measurements were performed on the same sample gas and control gas as in Measurement 1.
[0086] The results of the above measurements 1 to 3 will be explained. Figure 21(a) shows the detection response of the MSS with 42b-(Ni) sensitive membrane for measurement 1. As shown in Figure 21(a), very rapid responses (on the order of a few seconds) and measurable signals of various intensities were observed for all vapors. Figure 21(b) shows the average signal intensities for these vapors.
[0087] Interestingly, the 42b-(Ni) sensitive film showed strong responses to alkenes (hexane) and arenes (toluene), followed by good responses to carbonyl compounds (ethyl acetate, acetone) and alcohols (ethanol). In addition, when we look at the signal waveforms for these VOC vapors, we can see that they tend to reach saturation values in the early stages of the 30-second sampling period. In addition, the sensitivity of the 42b-(Ni) sensitive film to water vapor is much lower than that to VOC vapors. This is because, as described above for the measurement results using the 1-ox(27c-(Ni)) sensitive film-equipped MSS, water vapor has only minimal interaction with the porous 42b-(Ni) sensitive film, and the crystal structure of 42b-(Ni) also contains water in its cavities, which restricts the inclusion of more water in the nanoscale cavities.
[0088] Figure 22(a) shows the detection response of the MSS with 42b-(Ni) sensitive membrane for measurement 2. As shown in Figure 22(a), a very fast response (on the order of a few seconds) and measurable signals of various intensities were observed for all VOC vapors. Although the sensitivity to water vapor was very low, the signal was strong enough to clearly distinguish between the purging and sampling periods. Figure 22(b) shows the average signal intensities for these vapors.
[0089] As mentioned above, the difference between Measurement 1 and Measurement 2 is the type of solvent used in preparing the 42b-(Ni) sensitive film; DMSO was used in Measurement 1, and toluene was used in Measurement 2. Interestingly, in the results shown in Figures 22(a) and (b), a strong response was obtained for carbonyl compounds (ethyl acetate, acetone), followed by good responses for arenes (toluene), alkenes (hexane), and alcohols (ethanol). In addition, when focusing on the signal waveforms for these VOC vapors, it can be seen that for carbonyl compounds, the signal tends to reach saturation at the early stage of the 30-second sampling time, but for the other arenes, alkenes, and alcohols, the signal does not seem to reach saturation at the 30-second sampling time. Thus, the knowledge that the tendency of sensitivity to VOC vapors can change depending on the type of solvent used in preparing the sensitive film, even if the sensitive film uses the same molecule, can be an important guideline for optimizing the sensitive film in practical applications. However, it should be emphasized that such a change in sensitivity does not negate the usefulness of the sensitive film material (here, 42b-(Ni)) itself, and the fact remains that it has good sensitivity to various VOC vapors. On the contrary, the above characteristics are useful in that the solvent used in creating the sensitive film makes it possible to control the properties of the sensitive film, i.e., to optimize the response properties of the sensitive film, or to obtain multiple types of sensitive films that show different response properties to the measurement target from the same sensitive film material.
[0090] Figure 23(a) shows the detection response of the MSS with 42c-(Ni) sensitive membrane for measurement 3. As shown in Figure 23(a), a very rapid response (on the order of a few seconds) and measurable signals of various intensities were observed for all vapors. Figure 23(b) shows the average signal intensities for these vapors.
[0091] Interestingly, the 42c-(Ni) sensitive film used in this measurement showed a rapid and strong response to acetone, followed by almost equal responses to arenes (toluene) and alkenes (hexane), and also good responses to alcohol (ethanol) and ethyl acetate. In addition, when one focuses on the signal waveforms for these VOC vapors, one can see a tendency for the signal waveforms to reach saturation values in the early stages of the 30-second sampling time. The sensitivity of the 42c-(Ni) sensitive film to water vapor is much lower than the sensitivity to VOC vapors, as with the 27c-(Ni) and 42b-(Ni) sensitive films described above, and this tendency also applies to the 21c-(Ni) sensitive film described below. Therefore, one of the important features brought about by the porous structure of this compound system is the suppression of the inclusion of water in such nanoscale cavities.
[0092] In addition, in the above measurements 1 to 3, the number of droplets of each solution dropped onto the silicon film during MSS preparation was changed to 100 and 200, and the same response characteristics were obtained as in the case of 300 droplets. In addition, in all of the measurements 1 to 3, the sensitive film of each MSS was observed with an optical microscope before and after the measurement. It was found that all of the sensitive films maintained the same state as before the measurements even after the series of measurements, and no defects such as the sensitive film detaching from the silicon film were observed.
[0093] [Measurement 4] Using 21c-(Ni), an MSS with a 21c-(Ni) sensitive film was prepared in the same manner as in Measurement 1 above. However, in this measurement, an MSS chip with four channels (Ch1 to Ch4) was used, DMF was used as the solvent when preparing the sensitive film, and the number of droplets of the DMF solution on the silicon film of each channel was 10 for Ch1, 20 for CH2, 30 for Ch3, and 40 for Ch4. Ethyl acetate, ethanol, heptane, hexane, methanol, and toluene were used as VOCs in the sample gas, and measurements similar to those in Measurement 1 and measurements of control gases were performed.
[0094] Figure 24(a) shows the detection response of the MSS (Ch4) with 21c-(Ni) sensitive membrane for run 4. As shown in Figure 24(a), very rapid responses (on the order of a few seconds) and measurable signals of various intensities were observed for all vapors. Figure 24(b) shows the average signal intensities for these vapors.
[0095] Interestingly, the 21b-(Ni) sensitive film showed a very strong response to acetone and ethanol, with the sensitivity to ethanol exceeding that to acetone in terms of average signal intensity. It then showed a strong response to heptane and toluene, and also showed a good response to methanol and hexane. Thus, although the compounds of the present invention have a common feature of having excellent sensitivity to VOC vapors, the sensitivity to each VOC (as mentioned above, not only the static sensitivity in terms of the maximum signal intensity, but also the dynamic sensitivity in terms of the time-varying waveform of the signal) can change depending on the type and / or oxidation state of the substituents. This suggests that it may be possible to improve the accuracy of the measurement of the target detection target and the resolution (discrimination ability) between multiple detection targets by performing measurements using not only a single sensitive film material but also multiple sensitive film materials.
[0096] In addition, in this measurement, response characteristics similar to that of Ch4 described above were obtained from Ch1, Ch2, and Ch3. In addition, when the sensitive membrane of each channel of the MSS was observed under an optical microscope before and after the measurements, all sensitive membranes maintained the same condition as before the measurements even after the series of measurements, and no defects such as the sensitive membrane detaching from the silicon membrane were found.
[0097] [Measurement 5] Using the MSS with a 21c-(Ni) sensitive film prepared in the same manner as in measurement 4, the effect of the carrier gas contained in the sample gas and the humidity of the purge gas on the response characteristics of the MSS was analyzed. As samples, IPA (isopropyl alcohol) (hereinafter also referred to as "pure IPA" for convenience) and a solution in which toluene was dissolved in IPA at a predetermined concentration (hereinafter also referred to as "toluene-containing IPA solution") were used. Here, the sample gas was a mixed gas in which the headspace gas (IPA or saturated vapor of IPA containing toluene) in the container containing IPA or a toluene-containing IPA solution was sent out from the container by flowing a carrier gas (nitrogen gas) at a flow rate of 30 sccm, and this was mixed with a carrier gas (nitrogen gas) at a flow rate of 70 sccm to make a total flow rate of 100 sccm. Two types of nitrogen gas were used as the carrier gas: dry nitrogen gas and wet nitrogen gas prepared by passing dry nitrogen gas through water (i.e., blowing dry nitrogen gas into water). The actual humidity (moisture content) of the wet nitrogen gas was not measured. In addition, when dry nitrogen gas was used as the carrier gas, dry nitrogen gas was used as the purge gas, and when wet nitrogen gas was used as the carrier gas, wet nitrogen gas was used.
[0098] 25(a) to (d) are diagrams showing the detection responses of the MSSs (Ch1 to Ch4) with the 21c-(Ni) sensitive film when dry nitrogen gas was used as the purge gas and carrier gas in measurement 5. As shown in FIG. 25(a) to (d), in all channels, the toluene-containing IPA solution (toluene concentration: 10 -5 The sensitivity to M) was higher than that to pure IPA.
[0099] 26(a) to (d) are diagrams showing the detection responses of the MSSs (Ch1 to Ch4) with the 21c-(Ni) sensitive film when wet nitrogen gas was used as the purge gas and carrier gas in measurement 5. As shown in FIG. 26(a) to (d), when wet nitrogen gas was used, the toluene-containing IPA solution (toluene concentration: 10 -5 The sensitivity to toluene (M) was higher than that to pure IPA. Interestingly, when comparing channels with the same conditions for preparing the sensitive membrane (for example, comparing Figure 25(a) with Figure 26(a)), the signal output to the toluene-containing IPA solution was comparable, and the contribution of toluene contained in the sample gas was extremely small, whereas when wet nitrogen gas was used as the carrier gas and purge gas, the signal output to pure IPA tended to decrease compared to when dry nitrogen gas was used, while the presence or absence of toluene brought about a very large change in the signal output, unlike when dry nitrogen gas was used. As a result, in Figures 26(a) to (d) when wet nitrogen gas was used, the difference in the signal output value from MSS due to the presence or absence of toluene became clearer.
[0100] Next, the toluene concentration in the toluene-containing IPA solution was increased to 10 -5 M~10 -1 The same measurements were carried out after changing the concentration to M. The results are shown in FIG.
[0101] Figures 27(a) and (b) show the detection response of the MSS with 21c-(Ni) sensitive film (Ch2 and Ch1) when dry nitrogen gas was used as the purge gas and carrier gas, respectively. As shown in Figures 27(a) and (b), neither Ch2 nor Ch1 gave signal outputs different enough to distinguish the difference in toluene concentration in the toluene-containing IPA solution, and when the five types of signal waveforms are shown in one diagram, they are almost overlapped with each other. In other words, the sensitive film used here has low responsiveness to toluene in a dry nitrogen atmosphere.
[0102] 27(c) and (d) are diagrams showing the detection response of the MSS with a 21c-(Ni) sensitive film (Ch2 and Ch1) when wet nitrogen gas is used as the purge gas and carrier gas, respectively. Note that FIGS. 27(c) and (d) also show the detection response to pure IPA vapor. As shown in FIGS. 27(c) and (d), when wet nitrogen gas is used as the carrier gas and purge gas, the difference in signal intensity from the MSS due to the presence or absence of toluene becomes smaller when the toluene concentration is 10, as described above with reference to FIGS. 25 and 26. -5 Not only was this clear even for the very low concentration of M (0.9 PPM), but it was also clearly recognized over a wide range of toluene concentrations that the signal output value from the MSS tended to become higher as the toluene concentration increased, due to the difference in the toluene concentration in the toluene-containing IPA solution.
[0103] In this way, when the 21c-(Ni) sensitive film is used, not only is there no adverse effect of the MSS responding strongly to water vapor in the purge gas or sample gas, masking the contribution of other components to the signal from the MSS and preventing the detection of other components, but water vapor can also be used as a sensitizing additive to the purge gas or sample gas in order to increase the sensitivity of the MSS to certain components other than water vapor. Of course, the same effect of improving sensitivity can be obtained by adding water vapor only to the sample gas.
[0104] It should be noted that the signal intensities shown in Figures 27(c) and (d) appear to be generally lower than the signal intensities shown in Figures 27(a) and (b). This is because Figures 27(c) and (d) show signal intensities after baseline correction, whereas Figures 27(a) and (b) show signal intensities including DC offset without baseline correction. [Industrial Applicability]
[0105] As described above, the porphyrin metal complex according to the present invention has a porous structure, and can be advantageously used as a sensitive membrane for various sensors and other applications in which a porous structure is useful. This makes it possible to provide a sensitive membrane for detecting acetone or other sensitive membranes that exhibit high sensitivity even under high humidity conditions. [Prior art documents] [Patent documents]
[0106] [Patent Document 1] International Publication WO2011 / 148774A1 [Non-patent literature]
[0107] [Non-Patent Document 1] Evans, TA; Srivatsa, GS; Sawyer, DT; Traylor, TG Inorg. Chem. 1985, 24, 4733-4735. [Non-Patent Document 2] Bonfantini, EE; Burrell, AK; Campbell, WM; Crossley, MJ; Gosper, JJ; Harding, MM; Officer DL; Reid, DCWJ Porphyrins Phthalocyanines, 2002, 6, 708-719. [Non-Patent Document 3] Sharma S.; Nath, MJ Heterocycl. Chem., 2012, 49, 88-92. [Non-Patent Document 4] Aida, T.; Inoue, SJ Am. Chem. Soc. 1983, 105, 1304?1309. [Non-Patent Document 5] Aida, T.; Wada, K.; Inoue, S. Macromolecules 1987, 20, 237?241. [Non-Patent Document 6] Manke, A.-M.; Geisel, K.; Fetzer A.; Kurz, P. Phys. Chem. Chem. Phys. 2014, 16, 12029-12042.
Non-licensed Document 7
Non-licensed literature 9
Non-licensed literature 10
Non-licensed Document 11
Claims
1. Using a porphyrin metal complex having the following structure: A sensitive film material for a chemical sensor that responds to organic compound vapors of one or more organic compounds selected from the group consisting of acetone, ethanol, methanol, toluene, ethyl acetate, and hexane. 【Chemistry 1】
2. A sensitive film material for chemical sensors using a porphyrin metal complex having the following structure. 【Chemistry 2】
3. 3. The sensitive film material for chemical sensors according to claim 2, wherein the porphyrin metal complex has a saddle-shaped structure.
4. 4. The sensitive film material for a chemical sensor according to claim 2 or 3, which responds to organic compound vapors.
5. 5. The sensitive film material for chemical sensors according to claim 4, wherein the organic compound vapor is one or more organic compounds selected from the group consisting of carbonyl compounds, alcohols, alkenes, and arenes.
6. 5. The sensitive film material for a chemical sensor according to claim 4, wherein the organic compound vapor is acetone.
7. 3. The sensitive film material for a chemical sensor according to claim 1, wherein the chemical sensor detects a change in a physical parameter of the sensitive film.
8. The sensitive film material for chemical sensors according to claim 7, wherein the physical parameter is one parameter or a combination of multiple parameters selected from surface stress, stress, force, surface tension, pressure, mass, elasticity, Young's modulus, Poisson's ratio, resonant frequency, frequency, volume, thickness, viscosity, density, magnetic force, magnetic quantity, magnetic field, magnetic flux, magnetic flux density, electrical resistance, electrical quantity, dielectric constant, power, electric field, charge, current, voltage, electric potential, mobility, electrostatic energy, capacitance, inductance, reactance, susceptance, admittance, impedance, conductance, plasmon, refractive index, luminous intensity and temperature.
9. The sensitive film material for a chemical sensor according to claim 8 , wherein the chemical sensor is a surface stress sensor.
Citation Information
Patent Citations
Surface stress sensor
WO2011148774A1
Sensor having porous material or particulate material as receptor layer
WO2016121155A1